Why employees choose to stay or leave you: A case based study of Chinese employees' retention and turnover in a Japanese owned firm - Zhang, Bing (2010)
Abstract Children have played in an old man’s garden for several days. The old man is not happy with this. He wants the children will not come to his garden again. So he gives 25 pence to each child and says: ‘You let here become cheerfully that makes me feel younger and happy, so I pay you to show my appreciations about this.’ Children are so happy. The next day, they also come and play. The old man gives 15 pence to each child at the second day, and says: ‘Well done my good boys, but I am not very rich. So I can not give each one of you 25 pence in every day. Today I give you 15 pence each. Is that OK?’ The children are still happy with this. After 2 days, the old man reduces the payment to 5 pence each. The Children becomes quite angry and shout: ‘Just 5 pence? Do you know how hard we are working? We will not come again and play for you.’